2002
DOI: 10.1002/srin.200200208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alloying elements on the microstructure‐property relationship in thermomechanically processed C‐Mn‐Si TRIP steels

Abstract: The effect of additions of Nb, Al and Mo to Fe‐C‐Mn‐Si TRIP steel on the final microstructure and mechanical properties after simulated thermomechanical processing (TMP) has been studied. The laboratory simulations of discontinuous cooling during TMP were performed using a hot rolling mill. All samples were characterised using optical microscopy and image analysis. The volume fraction of retained austenite was ascertained using a heat tinting technique and X‐ray diffraction measurements. Room temperature mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…9 and 10) in the WM. This agrees closely with the findings in a number of investigations [11,12,18,24]. It was reported that a similar microstructure combination leads to a good combination of tensile strength and toughness.…”
Section: Group C (Mo Additions)supporting
confidence: 92%
“…9 and 10) in the WM. This agrees closely with the findings in a number of investigations [11,12,18,24]. It was reported that a similar microstructure combination leads to a good combination of tensile strength and toughness.…”
Section: Group C (Mo Additions)supporting
confidence: 92%
“…Bloch walls are temporarily pinned by lattice defects induced by strain hardening. High internal stresses are generated due to an incompatible transformation strain accompanying the martensitic (first order) transformation [7] which also affects the motion of magnetic domains. A further increase of magnetic field strength is needed to overcome the pinning effect and to increase magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in chemical composition has an effect on increasing the transformation tendency of steel g / ε during cooling from the hot working temperature, as confirmed in numerous scientific publications (3,4,(11)(12)(13)24,(29)(30)(31)(32)(33)(34)35,36). The difference in chemical composition has an effect on increasing the transformation tendency of steel g / ε during cooling from the hot working temperature, as confirmed in numerous scientific publications (3,4,(11)(12)(13)24,(29)(30)(31)(32)(33)(34)35,36).…”
Section: Thermo-mechanical Treatment Of High-manganese Austenitic Steelsmentioning
confidence: 83%